Predictors of External Whistleblowing: Organizational and Intrapersonal Variables - Sims, Randi L. (Journal of business ethics, 1998)
Research on whistleblowing has not yet provided a finite set of variables which have been shown to influence an employee's decision to report wrongdoing. Prior research on business ethics suggests that ethical business decisions are influenced by both organizational as well as intrapersonal variables. As such, this paper attempts to predict the decision to whistleblow using organizational and intrapersonal variables. External whistleblowing was found to be significantly related to supervisor support, informal policies, gender, and ideal values. External whistleblowing was not found to be significantly predicted by formal policies, organizational tenure, age, education, satisfaction, or commitment.